Guiding Principles for Establishing Energy Consumption Reduction and Increase Production Performance in Manufacturing - van Wyk, Gert; Naidoo, Vinessa; Edoun, E. Innocents (International Journal of Energy Economics and Policy, 2020)
This study provides a review, framework and guiding principles for constructing energy consumption reduction disciplines, with examples of application to international industries. It reviews the work of agencies and governments in creating energy efficiency models that help policy makers to assess changes in energy efficiency. A possibility to reduce costs incurred in product manufacturing and energy consumption constitutes energy-efficient consumption at industrial enterprises. The study justifies the performance indicators of industrial enterprises’ power supply systems. The estimates produced indicate that the largest portion of the potential energy savings is attributed to implementation of energy-saving projects. The study was performed at a manufacturing plant in South Africa with 489 respondents. It focused on energy usage in the manufacturing sector since this sector has always been the largest contributor to the GDP of South Africa. The results indicated that the proposed framework can not only reduce energy consumption but also increase production. Keywords: energy consumption, energy efficiency, framework. JEL Classifications: N77, N67, O14, P18 DOI: https://doi.org/10.32479/ijeep.8007